Trimethoprim-sulfamethoxazole in the treatment of gynecological tract infections - Ludmir Grimberg, Abraham (2015)
This work was performed in 61 patients with ginecológic tract infection, of which 51 received trimethoprim-sulfamethoxazole association at doses of 320 mg. and 16 gr. and 10 patients respectively as a comparative group received ampicillin 2 g. / day. In addition, 10 patients without morbidity postpartum received chemotherapeutic aforesaid association at the same doses, which serves as a control group. Treatment duration was 7 days; haematological and bacteriological studies were performed before and after treatment, discussing the results. In the group receiving morbid trimethoprim-sulfamethoxazole a clinical cure is observed in 42 cases (82.3%), of which 38 cases persistence of positive cultures was evident and in 9 cases (17.7%) with unfavorable clinical outcome. In the group that received ampicillin observed 8 cases (80%) with clinical cure of which 6 cases persisted positive culture and in 2 cases (20%) with unfavorable clinical course. In the group of patients not morbid 9 positive and 1 negative cultures found.